2023
DOI: 10.1108/afr-01-2023-0007
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural value chain participation and farmers' access to credit in northern Ghana

Timothy Anakwa Osei,
Samuel A. Donkoh,
Isaac Gershon Kodwo Ansah
et al.

Abstract: PurposePromoted for its inclusivity, agricultural value chain (AVC) financing leverages social capital and mechanisms such as off-take agreements and forward contracts to reduce borrowing and lending costs and risks for both farmers and lending institutions. AVC financing has been defined as the flow of financial products and services to and among the various actors within the AVC to address constraints of production and distribution and fulfill the needs of those involved in the chain by reducing risk and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Several studies have examined the determinants of credit demand and participation among farmers in various contexts. For instance, Osei et al (2019) found that factors such as farm size, education level, and access to extension services significantly influenced farmers' credit demand in Ghana. Similarly, Murendo et al (2020) identified factors such as land tenure security, risk perception, and distance to financial institutions as important 34 U.H.…”
Section: Determinants Of Agricultural Credit Demand and Participation...mentioning
confidence: 99%
“…Several studies have examined the determinants of credit demand and participation among farmers in various contexts. For instance, Osei et al (2019) found that factors such as farm size, education level, and access to extension services significantly influenced farmers' credit demand in Ghana. Similarly, Murendo et al (2020) identified factors such as land tenure security, risk perception, and distance to financial institutions as important 34 U.H.…”
Section: Determinants Of Agricultural Credit Demand and Participation...mentioning
confidence: 99%
“…Agricultural credit is impacted by the credit process or credit flow. Farmers who need credit for agricultural investments could not access it due to limited information on how to acquire the credit [32][33][34][35][36]. FIs can contribute to a positive impact on agricultural production improvement, but farmers still face difficulties in accessing credit due to the limited number of FIs willing to channel credit [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%